The Effort of Lecturers in Improving The Quality of Teaching Through Innovative and Creative Learning Strategies Based on Competence and Character in University - Fita Faridah; Muhammad Asrori (Jurnal PTK dan Pendidikan, 2021)
Competence and character need to be implemented considering the lack of lecturers through innovative and creative learning who are aware that competence and character are two things that must be balanced in an integrated manner in the learning process. The research method is qualitative research. The implementation of Islamic Religious Education learning is carried out in three stages, namely planning, implementing and evaluating learning. And the character values developed in PAI learning in the Informatics Engineering study program through competency-based active, innovative and creative learning include logical thinking, independent, hard work, working together, critically, confident, creative, logical thinking, mutual respect, understanding advantages and disadvantages of each student.